Fatigue damage detection using smart sensor - Fu, Wenhao. (2009)
In civil engineering field, huge amount of structural health monitoring work is required throughout the service life of the structures. In pursuing an autonomous, real-time and online non-destructive evaluation (NDE) method, piezo-impedance transducer (PZT) has attracted more and more attention from researchers in recent years. Although up to now, the real application of Electro-Mechanical Impedance (EMI) method with PZT on structure health monitoring is not utilized, experiments results shows its impressive potential. The main objective of this research is to investigate the ability of PZT patch to detect and characterize the damage on a simple, lab size structure induced by graduate wear (fatigue loading) produced by a 25 tons dynamic machine in the Construction Technology Laboratory. Studies conducted for this thesis were mainly experimental based.